Map of web access to series and films in Spain - Aguilar-Paredes, Carlos; Pérez-Montoro, Mario (Anuario ThinkEPI, 2015)
Audiovisual content has become a major leisure option in our society, and Internet has transformed its consumption patterns and market population. Identifying the websites that support this type of leisure activity is not a simple task. With data obtained from Alexa.com, it is possible to quantify the ecosystem of websites that provide links to audiovisual content in Spain.
Keywords: Downloads; Audiovisual content; Movies; Series; Audiences; Streaming; Links website.